2019
DOI: 10.1016/j.fbp.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline fractionation and enzymatic saccharification of wheat dried distillers grains with solubles (DDGS)

Abstract: The complete utilisation of Dried Distillers Grains with Soluble (DDGS) requires effective pretreatment strategies aiming to increase the enzymatic digestibility of cellulose and improve its conversion to fermentable sugars. To this end, the effect of different NaOH concentrations (0-5%, w/v) and temperature (30-121 o C) on the fractionation of DDGS to its main components (cellulose, hemicellulose, proteins) was evaluated. As the NaOH concentration and temperature increased, the total sugar content of the pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…First, DDGS is often subjected to hexane extraction to remove oil. After solid and liquid filtration, the residual DDGS is submerged into solvents aforementioned at certain temperatures for specific times, and then precipitation or centrifugation is conducted for protein recovery (Chatzifragkou et al, 2016; Gupta et al, 2016; Wang et al, 2009; Zaini et al, 2019). Gupta et al (2016) evaluated the differences in zein protein recovery using 13 different solvents (isopropanol, isoamyl alcohol, n‐butanol, isobutanol, 2,3‐butanediol, 1,4‐butanediol, tetrahydrofuran, 1,3‐dioxolane, 1,4‐dioxane, acetic acid, lactic acid, [emim]Ac, and [emim]Br) and found that isopropanol resulted in the highest extraction efficiency of 75%.…”
Section: Protein Extraction and Fractionationmentioning
confidence: 99%
See 2 more Smart Citations
“…First, DDGS is often subjected to hexane extraction to remove oil. After solid and liquid filtration, the residual DDGS is submerged into solvents aforementioned at certain temperatures for specific times, and then precipitation or centrifugation is conducted for protein recovery (Chatzifragkou et al, 2016; Gupta et al, 2016; Wang et al, 2009; Zaini et al, 2019). Gupta et al (2016) evaluated the differences in zein protein recovery using 13 different solvents (isopropanol, isoamyl alcohol, n‐butanol, isobutanol, 2,3‐butanediol, 1,4‐butanediol, tetrahydrofuran, 1,3‐dioxolane, 1,4‐dioxane, acetic acid, lactic acid, [emim]Ac, and [emim]Br) and found that isopropanol resulted in the highest extraction efficiency of 75%.…”
Section: Protein Extraction and Fractionationmentioning
confidence: 99%
“…Moreover, the acetic acid extraction protocol led to 98.9% kafirin purity, which is significantly higher than HCl–ethanol and NaOH–ethanol treatments (Wang et al, 2009). In the case of wheat‐DDGS, approximately 79% of protein content has been extracted into the liquid fraction using 5% NaOH treatment (Zaini et al, 2019).…”
Section: Protein Extraction and Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several protein extraction methodologies and conditions have been reported for integrated biorefineries. , Chemical methods include alkaline extraction, , aqueous ammonia (AFEX) extraction, , buffer extraction, organic solvent extraction, and combinations of these methods. , Alkaline extraction is commonly used for extracting proteins from agriculture residues, deoiled seedcakes, and DDGS with protein recoveries of 82–91.1%, 15–36%, and 60–79%, respectively. The efficacy of protein extraction using chemical methods depends on the nature of the biomass, solid-to-solvent ratio, temperature, pH, and process time . A recent review by Kumar et al summarized the effects of the sample-to-solvent ratio, alkali concentration, time, and temperature for several protein extractions from plant .…”
Section: Upstream Nitrogen Recovery From Biomassmentioning
confidence: 99%
“…A large amount of nonproteinaceous compounds are also present in the protein precipitate . Extraction of proteins from oilseed cakes has been done using hydrothermal and enzyme-assisted processes, followed by ultrafiltration and isoelectric precipitation, electrolyzed water treatment, alkaline precipitation, or acidic precipitation. ,, Extraction of proteins from DDGS and food wastes has been reported using alkaline, hydrothermal, and enzyme-assisted extraction, or coupling AFEX pretreatment and enzymatic extraction followed by acid precipitation …”
Section: Upstream Nitrogen Recovery From Biomassmentioning
confidence: 99%